Meta-analyses of chemotherapy for locally advanced and metastatic pancreatic cancer: results of secondary end points analyses - Sultana, A (Nature Publishing Group, 2008)
In advanced pancreatic cancer, level one evidence has established a significant survival advantage with chemotherapy, compared to best supportive care. The treatment-associated toxicity needs to be evaluated. This study examines the secondary outcome measures for chemotherapy in advanced pancreatic cancer using meta-analyses. A systematic review was undertaken employing Cochrane methodology, with search of databases, conference proceedings and trial registers. The secondary end points were progression-free survival (PFS)/time to progression (TTP) (summarised using the hazard ratio (HR)), response rate and toxicity (summarised using relative risk). There was no significant advantage of 5FU combinations vs 5FU alone for TTP (HR=1.02; 95% CI=0.85–1.23) and toxicity. Progression-free survival (HR 0.78; CI 0.70–0.88), TTP (HR=0.85; 95% CI=0.72–0.99) and overall response rate (RR=0.56; 95% CI=0.46–0.68) were significantly better for gemcitabine combination chemotherapy, but offset by the greater grade 3/4 toxicity thrombocytopenia (RR=1.94; 95% CI=1.32–2.84), leucopenia (RR=1.46; 95% CI=1.15–1.86), neutropenia (RR=1.48; 95% CI=1.07–2.05), nausea (RR=1.77; 95% CI=1.37–2.29), vomiting (RR=1.64; 95% CI=1.24–2.16) and diarrhoea (RR=2.73; 95% CI=1.87–3.98). There is no significant advantage on secondary end point analyses for administering 5FU in combination over 5FU alone. There is improved PFS/TTP and response rate, with gemcitabine-based combinations, although this comes with greater toxicity.